Integrating the Voices of Youth with Lived Experience as Co-researchers to Improve Research and Practice Approaches to Childhood Experiences of Intimate Partner Violence - Cullen, Olivia (Journal of family violence, 2023)
PurposeChildhood experiences of intimate partner violence (CEIPV) is common, but youth voices are underrepresented in such research, and little is known about what they find helpful in counselling. The purpose of this research was to engage youth with lived experience to address the following questions: (1) What do youth with CEIPV identify as key competencies needed for CEIPV service providers? And (2) How can youth participatory action research (YPAR) (and participatory methods) be utilized to enhance research on CEIPV? This article is focused on the YPAR process and addressing the second research question.MethodsUtilizing a YPAR approach, 12 Canadian youth were engaged as members of the research team to include their voices, perspectives, and experiences in addressing the research questions.ResultsYouth researchers highlighted strategies and principles to engage youth meaningfully in YPAR. These were: (1) recognizing and valuing lived experience as expertise; (2) recognizing the diversity in youths’ experiences, skills, and strengths; (3) creating a safe space with no judgement; and (4) having adult researchers committed to the process and not just the outcomes of the research.ConclusionsThe YPAR process used in the current study is an example of how youth with lived expertise successfully engage in research. Reflecting on what worked in the current study, youth researchers provided recommendations to improve youth engagement. When safety and relationships are prioritized, and youth feel heard and respected, they note finding value in participatory research to counter the impact CEIPV has had on their lives.